THE ROLE OF ISLAMIC EDUCATION IN THE FORMATION OF NATIONAL CHARACTER - Amal Fathullah; Muhammad Nur Effendi (Adisam Publisher, 2024)
Islamic education is a core component in shaping the nation's character based on noble moral, ethical and spiritual values. The study conducted in this research uses the literature research method. The results of the study show that Islamic education consistently educates values such as honesty, responsibility, truth, justice and respect for others, which are very important in the formation of individual character with integrity. Islamic education also plays a role in strengthening students' cultural and religious identity, promoting tolerance, mutual respect and social solidarity amidst the cultural and religious diversity of Indonesian society. In addition, the integration of modern knowledge and life skills in the Islamic education curriculum ensures that students develop not only moral qualities but also relevant competencies to face global challenges. However, challenges such as limited competent human resources, relevance of the curriculum to the needs of the times, and lack of funds and infrastructure, are obstacles that need to be overcome. Therefore, the implementation of strategies such as training and professional development for educators, development of relevant and applicable curricula, and investment in technology and adequate educational facilities, are essential to improve the quality of Islamic education. With this approach, Islamic education can effectively contribute to the formation of a superior and highly competitive national character in the global context.